Clinical Significance of Psoriasiform Sarcoidosis - Yanardag, Halil; Tetikkurt, Cuneyt; Bilir, Muammer; Tetikkurt, Seza; Askin, Ozge (Archives of Clinical and Medical Case Reports, 2020)
Sarcoidosis is a chronic granulomatous inflammatory disease characterized by the presence of noncaseating granulomas in various organs. Psoriasis is a persistent and recurrent autoimmune disorder mainly affecting the skin. Cutaneous involvement is observed in one fourth of the sarcoidosis patients and psoriatic plaques may be a manifestation of cutaneous sarcoidosis. The pathogenic mechanism of psoriasis is relevant to the overstimulation of CD4 TH1 and TH17 lymphocytes that are also involved in the granuloma formation of sarcoidosis. We present seven cases of sarcoidosis patients presenting with psoriasiform sarcoidosis. All the patients had cutaneous plaques indistinguishable from psoriasis. Diagnosis of sarcoidosis was confirmed by biopsy in at least two organs. Psoriasiform sarcoidosis was identified by skin biopsy of the involved cutaneous lesions. All patients had stage III sarcoidosis and presented with one or more clinical or laboratory manifestations of sarcoidosis. BAL was negative for infectious agents. Histopathologic examination of the bronchial and transbronchial biopsy samples revealed noncaseiting granulomatous inflammation. Differentiation of sarcoidosis and psoriasis may constitute a diagnostic dilemma for the clinician in terms of the identical skin lesions. The presence of psoriatic plaques may suggest an overlap between the underlying pathogenetic mechanisms of both disorders. Despite the great clinical similarity, the only way to differentiate the two syndromes is pathological examination. The common pathogenetic mechanism involving the TH1 and TH17 pathways for both sarcoidosis and psoriasis may be the fundamental linkage for this occurrence. We present seven cases of sarcoidosis patients presenting with psoriasiform lesions to define the clinical profile of sarcoidosis in these patients including presentation, laboratory findings and prognosis. The coexistence of sarcoidosis and psoriasis, on the other hand may s